Detailed genetic analyses highlight genetic variation and genomic regions for lead tolerance in spring wheat - Mourad, Amira M. I.; Sallam, Ahmed; Farghaly, Khaled A.; Börner, Andreas (Frontiers in Agronomy, 2025)
IntroductionUnderstanding the dynamics of Pb tolerance across different growth stages is essential for breeding wheat varieties with comprehensive tolerance to Pb contamination throughout their life cycle. Lead (Pb) in soil affects wheat plants at all growth stages. However, the seedling stage is considered a sensitive growth stage for the tolerance of most abiotic stresses. Genetic variation in lead tolerance is poorly understood, and genetic control has still not been investigated.MaterialsIn this study, 103 highly diverse wheat genotypes were investigated under normal and lead stress conditions at the seedling stage. Different seedling growth traits were scored under each treatment. GWAS was performed via two different sets of markers: 21,750 (25K Infinium iSelect array) and 37,790 SNPs (genotyping-by-sequencing) to identify SNP markers associated with the studied seedling traits.ResultsHigh genetic variation was found among all the genotypes for all the traits. High broad-sense heritability estimates ranging from 0.25-0.93 were observed. A highly significant correlation was found among all the traits scored under normal and lead stress conditions. Low or no significant phenotypic correlations were found for lead tolerance between the seedling and adult growth stages. A set of eight genotypes were classified as lead-tolerant genotypes. The GWAS revealed a set of 222 significant markers associated with lead tolerance. Markers with pleiotropic effects were detected under Pb stress and between lead and normal conditions. Interestingly, five significant markers were found to be associated with lead tolerance at the seedling and adult growth stages.DiscussionThe results of this study provide new and novel insights into genetic control and genetic variation in lead tolerance at the early growth stage. All the genes and genotypes reported in this study will be very useful for further investigations of lead tolerance in wheat at different growth stages.